2,4-Dihydroxy-3'-methoxy-4'-ethoxychalcone suppresses cell proliferation and induces apoptosis of multiple myeloma via the PI3K/akt/mTOR signaling pathway - FengChen Zhu; DianMing Jiang; MingHua Zhang; Bo Zhao (Taylor & Francis Group, 2019)
Context: Caragana pruinosa Kom. (Fabaceae), a commonly used folk medicine, has been found to possess antitumor effects. However, the antiproliferative effect of 2,4-dihydroxy-3'-methoxy-4'-ethoxychalcone (DMEC) derived from C. pruinosa against multiple myeloma (MM) has never been investigated. Objective: This study systematically evaluates the antiproliferative effect of DMEC against MM cells. Materials and methods: The antiproliferative effect of DMEC (1, 2, 4, 8, 16, 32, and 64 μM) on MM cells lines, including RPMI8226, MM.1S, and U266, was examined using Cell counting kit-8 (CCK-8) assay after 24 h incubation. The proapoptotic effect of DMEC (20 μM) was determined using fluorescent microscope and flow cytometer, and its possible underlying mechanisms were further studied by using western blotting analysis. Results: The half maximal inhibitory concentrations (IC50) of DMEC on RPMI8226, MM.1S, and U266 cells were calculated as 25.97, 18.36, and 15.02 μM, respectively. The inhibitory effect of DMEC on MM cells was related to mitochondria-mediated apoptosis via upregulation of the cleaved-caspase-3 (C-3), cleaved-caspase-9 (C-9), Bad, and cytochrome C (Cyto C), but downregulation of the Bcl-2 and poly ADP-ribose polymerase (PARP). Furthermore, DMEC (5, 10, and 20 μM) reduced the expression of phosphatidylinositol-3-kinase (PI3K), phosphorylated (p)-protein kinase B (Akt), and p-mammalian target of rapamycin (p-mTOR), which were further evidenced by pretreatment with IGF-1, a PI3K activator. Conclusion: Collectively, our results indicate that the DMEC could be treated as a new candidate for treatment of multiple myeloma in the future. Also, an in vivo study is warranted in the future.